P-117 Combination Therapy with Immunomodulator and Infliximab is Associated with Higher Infliximab Trough Levels and Decreased Likelihood of Antibody Formation. (February 2017) - Zitomersky, Naamah; Chi, Lisa; Bender-Stern, Julia; Tollefson, Sophia; Naik, Snehal; Snapper, Scott; Bousvaros, Athos
Abstract : Background: Infliximab therapy for inflammatory bowel disease (IBD) is limited by the development of loss of response, resulting in a change of medication. Previous studies in adults correlate loss of response (LOR) with the development of antibodies to infliximab (ATI) and low serum trough levels of infliximab (IFXL). Combination therapy with an immunomodulator (i.e., thiopurine or methotrexate) and infliximab has been shown to decrease ATI formation in adult studies, but the risks and benefits of combination therapy remain unclear. There is a paucity of prospective pediatric data evaluating the relationship between ATI, IFXL, immunomodulator use, and LOR. Methods: We performed a single center prospective observational cohort study of 227 pediatric and young adult patients currently receiving infliximab. During clinical visits for infusions, an additional serum sample was obtained for research assay of IFXL and ATI. Practicing physicians could order infliximab levels as clinically indicated, but were blinded as to the results of the research samples. At the time serum was obtained, demographics, disease phenotype and activity, duration of infliximab therapy, use of combination therapy (methotrexate or 6-mercaptopurine with infliximab) and LOR (defined by discontinuation of infliximab) were recorded. P values are based on a Fisher's exact test or Mann-Whitney's test. Results: ATI and IFXL were measured biannually from 227 patients (138 male; mean age 16.9 ± 4.4 yr; 189 Crohn's disease [CD], 35 ulcerative colitis [UC], and 3 indeterminate colitis). Infliximab use ranged from 40 days to 14.9 years: median 5.1 years (interquartile range [IQR] [3.5–7.1]) and median study follow-up period was 3.3 years (IQR [2.0–3.7]). Fifty-eight of 227 (25%) had ATI ≥3.1 U/mL at least once during the follow-up period. Thirty-three of 227 (14%) had LOR during the follow-up period. LOR was more likely to occur in subjects with an ATI ≥3.1 U/mL (23/58; 40%) compared to an ATI <3.1 U/mL (10/169; 6%) ( P = 0.0001). At the patients' most recent study visit, 85 of 227 (37%) were on combination therapy with 14 on 6-mercaptopurine and 71 on methotrexate, while 142 of 227 (63%) were on infliximab monotherapy. Nine of 85 (11%) patients on combination therapy had ATI ≥3.1 U/mL compared to 29 of 142 (20%) on monotherapy ( P = 0.07). Within the combination therapy group, ATI ≥3.1 U/mL was present in 3 of 14 (21%) patients on 6-mercaptopurine versus 6 of 71 (8%) patients on methotrexate ( P = 0.2). In patients receiving 5 to 10 mg/kg of infliximab every 8 weeks, median IFXL was higher in those patients on concurrent immunomodulator therapy (9.0 [IQR 7.4–15.7]) versus those who were not (6.5 [IQR 2.2–10.7]) ( P = 0.008). Conclusions: In this prospective blinded study, the development of ATI was associated with a higher likelihood of LOR to infliximab. Combination therapy with immunomodulator was associated with increased infliximab trough levels. There was a trend suggesting a higher likelihood of ATI in the monotherapy group compared to the combination therapy group ( P = 0.07). Concomitant immunomodulatory therapy may reduce the likelihood of LOR, perhaps by increasing infliximab levels and reducing the likelihood of antibody formation.